[Passport fixing 2 ; Blanco, Jose ; Generics [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Discusses the passport irregularities that happened in the Department of Foreign Affairs ; interview with Pitok, an artist about his work and family ; Senate Bill 453 requiring all doctors to prescribe generic drugs.
Passport fixing 2 ; (16 min.) -- Blanco, Jose (17 min.) -- Generics (15 min.)
VHS.
Keywords: Blanco, Jose; Philippines. -- Department of Foreign Affairs -- Corrupt practices; Passports -- Philippines; Drugs -- Generic substitution -- Law and legislation -- Philippines -- Philippines